Investigating the Relationships between Habitat Parameters and Species Diversity of Carabidae (Coleoptera: Carabidae): A Case Study of Alborz Province - Arash Eshkoob; Jamasb Nozari; Soheil Eagderi (تاکسونومی و بیوسیستماتیک, 2022)
The present study was conducted to investigate the effects of physical factors on the diversity of species of Carabidae (Coleoptera: Carabidae) in three regions of Karaj, Eshtehard, and Taleghan, Alborz province. To this end, during 2015-2016, sampling was carried out using pitfall traps and physical factors. In this regard, the elevation, slope, direction, precipitation, temperature, soil texture, grain size of soil, and percentage of vegetation were recorded in each studied station. Based on the results, in total, 329 specimens including 38 species were identified in the three studied areas. Pearson and Spearman tests were used to investigate the relationships between the species diversity index (Shannon's Diversity Index) and the studied factors. Also, the effect of habitat physical parameters on the diversity of the species of Carabidae in the studied areas was analyzed using Canonical Correspondence Analysis (CCA). The results of the study showed that no significant relationship between the Shannon-Wiener Index and studied parameters (P<0.05). Species diversity was affected by temperature, the three parameters of altitude, soil texture, and grain size of soil, and the four parameters of direction, slope, precipitation, and vegetation percentage in Karaj, Eshtehard, and Taleghan, respectively.